ANALYSIS OF OVERWEIGHT, OBESITY, PHYSICAL ACTIVITY LEVELS, AND SELF-ESTEEM IN CHILDREN FROM LEÓN, NICARAGUA - Reyes Ortiz, Ricardo (2018)
The objective of this investigation was to analyze the prevalence of overweight or obesity, the levels of physical activity and self-esteem in a Nicaragua school region. 731 students from 10 schools in the department of Leon Nicaragua were evaluated: 260 were in fourth grade, 226 in fifth grades and 245 in sixth grades, between 9 and 13 years old. Height and weight evaluation to calculate BMI, the Physical Activity Questionnaire for Older Children (PAQ-C), and Lawrence Self-Esteem Questionnaire (LAWSEQ) were applied. According to the results, 25% of students have a prevalence of overweight and obesity and 4% in low weight. In physical activity, 77% perceive themselves to be moderately active. Regarding self-esteem, it was found that 51% had low self-esteem and only 4% had a high level of self-esteem. This directs the course for the development of interventions that contemplate the school environment, in order to promote strategies that activate lifelong childhood to a healthier lifestyle.